Survival impact of pre-treatment neutrophils on oropharyngeal and laryngeal cancer patients undergoing definitive radiotherapy - Sumner, Whitney A. (J Transl Med, 2017)
BACKGROUND: Squamous cell carcinoma of the head and neck (HNSCC) represents an array of disease processes with a generally unfavorable prognosis. Inflammation plays an important role in tumor development and response to therapy. We performed a retrospective analysis of HNSCC patients to explore the relationship of the lymphocyte and neutrophil counts, the neutrophil-to-lymphocyte ratio (NLR) overall survival (OS), cancer-specific survival (CSS), local control (LC) and distant control (DC). MATERIALS/METHODS: All patients received definitive treatment for cancers of the oropharynx or larynx between 2006–2015. Neutrophil and lymphocyte counts were collected pre-, during-, and post-treatment. The correlations of patient, tumor, and biological factors to OS, CSS, LC and DC were assessed. RESULTS: 196 patients met our inclusion criteria; 171 patients were Stage III or IV. Median follow-up was 2.7 years. A higher neutrophil count at all treatment time points was predictive of poor OS with the pre-treatment neutrophil count and overall neutrophil nadir additionally predictive of DC. Higher pre-treatment and overall NLR correlated to worse OS and DC, respectively. CONCLUSION: A higher pre-treatment neutrophil count correlates to poor OS, CSS and DC. Lymphocyte counts were not found to impact survival or tumor control. Higher pre-treatment NLR is prognostic of poor OS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-017-1268-7) contains supplementary material, which is available to authorized users.